Biochemical characteristics of some varieties of peach and nectarine grown in Sochi - Yu. S. Abilfazova (Новые технологии, 2024)
Biochemical characteristics and features of the most promising varieties of stone fruit crops (peach, nectarine) submitted for research have been shown. Biochemical analyzes of peach and nectarine fruits grown in the humid subtropics of Russia were carried out in 2019-2020 at the Subtropical Scientific Center of the Russian Academy of Sciences in the Laboratory of Plant physiology and Biochemistry. The following varieties were used for biochemical analyzes: Rannyaya zarya, Larisa (control one), Osenniy rymyanets, Anton Chekhov, Big Top, Nectarine Sklor. The content of biologically valuable substances in stone fruits, which determine not only their taste characteristics, but also their nutritional and therapeutic and prophylactic effects, is a criterion for high commercial quality of products. That is why we are faced with the task of assessing the chemical composition of peaches and nectarines, which directly depends on weather and climate conditions, varietal characteristics, place of growth, etc. It is known that the pulp of peaches and nectarines contains a large amount of sugars, organic acids (mainly malic), vitamins, enzymes, macro- and microelements. In assessing the taste qualities of peaches and nectarines, the content of sugars, acids and vitamin C (or ascorbic acid), which acts as an antioxidant, is of great importance. Biochemical analysis of peach and nectarine fruits revealed the maximum sugar content - 10.16% in the Larisa variety (control one) of mid-late ripening period, the minimum in the Rannyaya Zarya variety of early ripening period, which is significantly lower by 1.3 times compared to the control one. High vitamin C content in the Larisa variety fruits was noted - up to 16.56 mg%, which is significantly higher than other studied varieties by 2.60-5.19 mg%. Promising varieties Larisa and Anton Chekhov were distinguished by a balanced taste of fruits and resistance to abiotic factors of the environment of the Black Sea coast of Russia.